PROSES MORFOLOGIS PADA ANTOLOGI PUISI RANTING KERING KARYA SANTOSO WURYANDOKO - Utami, Mega; Zulfahita; Wirawan, Gunta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the researcher’s desire to know the morphological process of the Dry Branch Poetry Anthology by Santoso Wuryandoko, which includes the affixation process, reduplication process, and composition process. The problem in this research is how the affixation process, reduplication process, composition process in the dry twig poetry anthology by Santoso Wuryandoko and its implementation in learning. The aim of this research is to describe the morphological process, namely the affixation process, reduplication process, and composition process in the dry twig poetry anthology by Santoso Wuryandoko, as well as its implementation in Indonesian language learning. This research method is a descriptive method with qualitative form. The analysis teachnique uses listening and note taking techniques. Checking the validity of the data, persistence of observations, triangulation and adequacy of references. The results of research on the Morphological Process in the Dry Branch Poetry Anthology by Santoso Wuryandoko can be concluded: (1) There are three types of affixation, namely prefixes, suffixes, and confixes. (2) there are two types of reduplication, namely complete reduplication and partial reduplication. (3) there are two types of composition or compound words, namely equivalent compound words and unequal compound words.